2010
DOI: 10.1007/s12070-010-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Coblation assisted excision of lingual thyroid

Abstract: Lingual thyroid (LT) tissue is the most frequent ectopic location of the thyroid gland. We report 5 cases of symptomatic LT and discuss the new surgical approach. Transoral approach and coblation assisted excision of LT was performed. Postoperative follow-up for all patients was like as tonsillectomy management without tracheotomy. It's seem that this approach is much better than other such as tongue-splitting, transcervical transhyoid, pharyngotomy, with an infrahyoid approach, combined cervical and intraoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Lingual thyroid tissue is the most frequent ectopic location of the thyroid gland, although its clinical incidence is low with 1 in 100 000 cases occurring [ 4 ]. There are four groups of lingual thyroid: lingual, sublingual, thyroglossal, and intralaryngeal [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lingual thyroid tissue is the most frequent ectopic location of the thyroid gland, although its clinical incidence is low with 1 in 100 000 cases occurring [ 4 ]. There are four groups of lingual thyroid: lingual, sublingual, thyroglossal, and intralaryngeal [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Terris et al [10] reported that transoral minimal invasive lingual thyroid resection decreased morbidity and duration of hospitalization compared to other open approaches. Coblation assisted lingual thyroid and lingual tonsil resection techniques were used and successful results were reported [11][12][13]. Leitzbach et al [12] reported successful results and low complication rates in 108 patients undergoing coblation assisted resection due to tongue root and lingual tonsil hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Lingual thyroid tissue is the most frequent ectopic location of the thyroid gland, although its clinical incidence is low with 1 in 100 000 cases occurring. 10 There are four groups of lingual thyroid: lingual, sublingual, thyroglossal, and intralaryngeal. Endocrine changes such as puberty, pregnancy, and menstruation can lead to an increase in gland size and symptoms.…”
Section: Discussionmentioning
confidence: 99%